2012
DOI: 10.1073/pnas.1207653109
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for promiscuity and specificity during Candida glabrata invasion of host epithelia

Abstract: The human pathogenic yeast Candida glabrata harbors more than 20 surface-exposed, epithelial adhesins (Epas) for host cell adhesion. The Epa family recognizes host glycans and discriminates between target tissues by their adhesin (A) domains, but a detailed structural basis for ligand-binding specificity of Epa proteins has been lacking so far. In this study, we provide high-resolution crystal structures of the Epa1A domain in complex with different carbohydrate ligands that reveal how host cell mucin-type O-g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
119
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(123 citation statements)
references
References 26 publications
4
119
0
Order By: Relevance
“…Studies using carbochips (glycan arrays) have shown that Epa1, Epa6, and Epa7 bind to oligosaccharides that contain terminal galactose residues, such as those occurring in mucin-type O-glycans (22,31). This is consistent with the idea that these proteins enable the fungus to bind to glycoproteins on the host cell surface.…”
Section: Candida Glabrata Adhesinssupporting
confidence: 65%
See 3 more Smart Citations
“…Studies using carbochips (glycan arrays) have shown that Epa1, Epa6, and Epa7 bind to oligosaccharides that contain terminal galactose residues, such as those occurring in mucin-type O-glycans (22,31). This is consistent with the idea that these proteins enable the fungus to bind to glycoproteins on the host cell surface.…”
Section: Candida Glabrata Adhesinssupporting
confidence: 65%
“…For instance, heterologous expression studies in S. cerevisiae showed that adherence of C. glabrata to epithelial and endothelial cells is mediated, at least in part, by the proteins encoded by the EPA gene family (7,22,27,28). Recently, fungal adhesin research has moved toward more structural studies using nanotechnology in which X-ray crystallography, nuclear magnetic resonance (NMR), and atomic force microscopy (AFM) are used to obtain detailed information with respect to the structure and ligand-binding specificities of adhesins in C. albicans, C. glabrata, and S. cerevisiae (termed flocculins in the last-named organism) (29)(30)(31)(32)(33). Clearly, these highresolution approaches largely improve our understanding of how fungal adhesins modulate adhesion, aggregation, biofilm formation, and host-immune responses.…”
Section: Adhesins Are Outer-surface Components Of the Fungal Cell Wallmentioning
confidence: 99%
See 2 more Smart Citations
“…Salivary glycans have been shown to have a protective effect against Candida albicans-an organism able to bind a range of mucin oligosaccharide structures, acting as binding decoys and removing the organisms in the saliva before they can attach to the oral surface (20). Pathogenic Candida glabrata, the second most common cause of candidiasis, has been shown, by glycan microarray analysis, to bind to terminal galactose residues (64). The Western blotting and PAS staining analyses in our study suggested a reduction in glycosylation on salivary mucins, and LC-MS/MS analysis showed an increase in neutral structures with terminal galactose residues, both of which are likely to increase candidiasis.…”
Section: Discussionmentioning
confidence: 99%